Tacrolimus and Cyclosporine A Inhibit Allostimulatory Capacity and Cytokine Production of Human Myeloid Dendritic Cells. (1st September 2001) - Szabo, Gyongyi; Gavala, Cristina; Mandrekar, Pranoti
Abstract : Myeloid dendritic cells (DCs) are pivotal in the recognition of alloantigens and, therefore, in the induction of allograft rejection. Induction of alloreactive T cell proliferation by myeloid DCs depends on the maturation of DCs, the expression of costimulatory molecules, and the cytokine environment. This study investigated the effects of tacrolimus and cyclosporine A (CsA) on DC maturation and allostimulatory capacity. Myeloid DCs were propagated from normal blood monocytes with interleukin (IL) 4 and GM-CSF for 7 days in the presence or absence of tacrolimus (FK506; 10 nM) or CsA (1 μg/mL). Exposure of DCs during maturation to tacrolimus or CsA resulted in no significant change in the expression of DC phenotypic markers, including CD80, CD86, and HLA Class I and II antigens determined by flow cytometry. T cell proliferation in one-way, mixed-leukocyte reaction experiments revealed a decreased allostimulatory capacity of DCs that matured in the presence of tacrolimus or CsA compared with untreated controls ( P <0.02). Production of inflammatory cytokines, tumor necrosis factor α ( P <0.04) and IL-12 ( P <0.04) in response to lipopolysaccharide (1 μg/mL) or staphylococcal enterotoxin B (1 μg/mL) induction was significantly reduced in DCs exposed to tacrolimus or CsA during maturation. In contrast, production of the immuninhibitory cytokine IL-10 was not decreased in tacrolimus- or CsA-treated DCs. These results suggest that tacrolimus and CsA inhibit the allostimulatory capacity of in vitro-generated myeloid DCs without significant effects on DC phenotypic maturation. Decreased production of IL-12 and tumor necrosis factor α, but not of IL-10, is likely to contribute to the impaired accessory-cell function of tacrolimus- and CsA-treated DCs. Thus, tacrolimus and CsA can inhibit recognition of alloantigens by decreasing the accessory-cell capacity of monocyte-derived myeloid DCs.